PENGARUH MEDIA EDUGAME BAAMBOOZLE TERHADAP HASIL BELAJAR IPAS KELAS V DI SD NEGERI 195 PALEMBANG - Chamelia, Nadia; Murjainah; Oktavia, Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of bamboozle edugame media on the learning outcomes of science subjects on diversity and cultural heritage of class V of SD Negeri 195 Palembang. The problems found were caused by the use of learning media that were less interesting and interactive, resulting in low science subjects learning outcomes of class V of SD Negeri 195. This study used a quantitative experimental method with the True-Experimental Design technique in the form of Pretest-Posttest Control Group Design. The sample used in this study was class V.A students as the experimental class totaling 30 students, and class V.B students as the control class totaling 30 students. Data collection techniques used tests and documentation. Data analysis used normality, homogeneity, and hypothesis tests. Based on the results of the study showed that the results of the final test (posttest) in the experimental class that was given treatment using the baamboozle edugame media obtained an average value of 82.33 and the control class obtained an average value of 68.33. In addition, based on the results of hypothesis testing using the t-test (Independent Sample T-Test) the results obtained were that the t-count value > t-table, namely 5.709 > 2.001 or the significance value of t-count 0.000 < t-table 0.05, which means Ha is accepted and Ho is rejected, it can be concluded that there is an influence of the use of baamboozle edugame media on the learning outcomes.